2007
DOI: 10.1007/s10517-007-0352-z
|View full text |Cite
|
Sign up to set email alerts
|

Antiaggregant effects of biogenic chloramines

Abstract: Alanine and taurine sharply potentiate antiaggregant effects of hypochlorite on platelets in platelet-rich plasma. This effect is determined by more pronounced action of chloramine derivatives, products of interaction of added amino acids with hypochlorite. Platelets are more sensitive to the inhibitory effects of amino acid chloramine derivatives (biogenic chloramines) compared to erythrocytes and neutrophils. The antiaggregant effects of biobenic amines, as covalent platelet inhibitors, in platelet-rich plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 17 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…These antiaggregants inhibit platelet functions via chemical modifi cation of molecular targets in cells. Acetylsalicylic acid (aspirin) reacting with prostaglandin H 2 -synthase [9], and thienopyridines [10,11], whose metabolites react with sulfhydryl group of ADP receptors, are widely used in clinical practice.We previously proposed to use chloramine derivatives of biogenic compounds, mainly of amino acids and taurine, as covalent antiaggregants [1][2][3]5]. Their specifi c feature is inhibition of platelet functions in all mechanisms of cell activation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These antiaggregants inhibit platelet functions via chemical modifi cation of molecular targets in cells. Acetylsalicylic acid (aspirin) reacting with prostaglandin H 2 -synthase [9], and thienopyridines [10,11], whose metabolites react with sulfhydryl group of ADP receptors, are widely used in clinical practice.We previously proposed to use chloramine derivatives of biogenic compounds, mainly of amino acids and taurine, as covalent antiaggregants [1][2][3]5]. Their specifi c feature is inhibition of platelet functions in all mechanisms of cell activation.…”
mentioning
confidence: 99%
“…It is therefore interesting to study the capacity of covalent antiaggregants to react with different blood components, primarily serum albumin [14]. Amino acid chloramines should react with sulfhydryl group and surface thioester groups of serum albumin methionine [5]. The possibility of binding of these antiaggregants by serum albumin is not yet studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Murina et al showed that taurine alone in a concentration of 10 mM failed to change platelet aggregation in PRP from healthy donors, while in combination with 1 mM sodium hypochlorite (NaOCl) it potentiated the antiaggregant effect of NaOCl by 1.7 times, following stimulation with 10 µM ADP. Further, incubation of PRP with DT (0.25 mM) inhibited platelet aggregation to the same extent as 1 mM NaOCl [136]. Another finding of this study, obtained from experiments not performed on humans but on animals (rabbit PRP), showed that biogenic chloramines are able to elicit a high initial selectivity for platelet surface binding (result expressed as a higher rate constant of chloramines interaction with platelet receptors, than that achieved when attaching to plasma proteins receptors) [136].…”
Section: Evidence From Human Studiesmentioning
confidence: 85%
“…To sustain the antiplatelet effect of DT, Murina et al demonstrated, in an in vitro study using a kinetic nephelometric technique, that DT can also suppress the initial ADP-induced platelet aggregation (formation of small aggregates) in rabbit platelets, and that its effect may be ascribed to platelet sulfhydryl groups changes [135]. DT in a concentration of 10 µM reduced by half the intensity of small-angle light scattering aggregation triggered by 0.2 µM ADP in isolated rabbit platelets, while DT addition in a moderate concentration (10 millimoles/L) to rabbit blood was shown to markedly inhibit the impedance measured by whole blood aggregometry, triggered by 10 µM ADP [136]. A rank of efficacy in suppressing initial aggregation of isolated rabbit platelets was established for several taurine chloramine derivatives.…”
Section: Evidence From Animal Studiesmentioning
confidence: 93%